2008
DOI: 10.1111/j.1471-0528.2008.01756.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐arm blood pressure differences in pregnant women

Abstract: Objective To determine the prevalence of blood pressure interarm difference (IAD) in early pregnancy and to investigate its possible association with maternal characteristics.Design A cross-sectional observational study.Setting Routine antenatal visit in a university hospital.Population A total of 5435 pregnant women at 11-14 weeks of gestation.Methods Blood pressure was taken from both arms simultaneously with a validated automated device.Main outcome measures The presence of inter-arm blood pressure differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 16 publications
(29 reference statements)
1
37
0
1
Order By: Relevance
“…Kolmogorov-Smirnov analysis showed that the IAD prevalences were not normally distributed methods of BP measurements Tables 2 and 3 provide differences between groups separated for measurement methods (simultaneous vs. sequential measurements), device (manual vs. automatic) and the number of readings (1 vs. 2 or more readings) used to determine IAD prevalences ( Table 2), average and absolute IAD values ( Table 3). There were 12 studies 8,9,13,14,17,18,24,26,28,29,31,32 (n = 8,853) in which simultaneous measurements and 12 studies 13,14,16,[19][20][21][22][23]25,27,30,33 (n = 6,001) in which sequential measurements were performed, which means that in two studies 13,14 both methods were assessed. In 14 studies an automated oscillometric device 8,9,13,14,[17][18][19][26][27][28][29][30][31][32] (n = 12,644) was used for IAD determination, in seven studies 9,17,20,27,…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Kolmogorov-Smirnov analysis showed that the IAD prevalences were not normally distributed methods of BP measurements Tables 2 and 3 provide differences between groups separated for measurement methods (simultaneous vs. sequential measurements), device (manual vs. automatic) and the number of readings (1 vs. 2 or more readings) used to determine IAD prevalences ( Table 2), average and absolute IAD values ( Table 3). There were 12 studies 8,9,13,14,17,18,24,26,28,29,31,32 (n = 8,853) in which simultaneous measurements and 12 studies 13,14,16,[19][20][21][22][23]25,27,30,33 (n = 6,001) in which sequential measurements were performed, which means that in two studies 13,14 both methods were assessed. In 14 studies an automated oscillometric device 8,9,13,14,[17][18][19][26][27][28][29][30][31][32] (n = 12,644) was used for IAD determination, in seven studies 9,17,20,27,…”
Section: Description Of Studiesmentioning
confidence: 99%
“…8,9,13,16-20,23-33) (n = 14,047) and 13 studies 9,16,17,[19][20][21][22]25,27,29,30,32,33 (n = 6,508), respectively. Seventeen studies 8,9,16,17,[19][20][21][22]24,25,[27][28][29][30][31][32][33] (n = 12,956) showed the number of subjects with a diastolic IAD ≥10 mm Hg and six studies 9,17,20,27,32,33 (n = 4,447) a diastolic IAD ≥20 mm Hg. Systolic IAD values (right-left BP values) were provided or could be calculated in 11 studies 9,14,17,21,25,28-33 (n = 8,109).…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…6 They also noted that the prevalence and magnitude of inter-arm variation increases with increasing blood pressure. The authors have concluded that by measuring blood pressure in one arm only, there is a chance of underreporting hypertension.…”
mentioning
confidence: 98%
“…Poon et al have introduced us to another variable-which arm was interrogated-that can influence our ability to predict and prevent eclampsia and its sequelae. 6 Despite these shortcomings, office-based blood pressure measurement is the standard for screening for hypertensive disorders in pregnancy. This detection method has been the entry point for all the epidemiological studies and treatment trials performed up to this point.…”
mentioning
confidence: 99%